Acyldepsipeptide Probes Facilitate Specific Detection of Caseinolytic Protease P Independent of Its Oligomeric and Activity State. (7th January 2020) - Eyermann, Barbara; Meixner, Maximilian; Brötz‐Oesterhelt, Heike; Antes, Iris; Sieber, Stephan A.
Abstract: Caseinolytic protease P (ClpP) is a tetradecameric peptidase that assembles with chaperones such as ClpX to gain proteolytic activity. Acyldepsipeptides (ADEPs) are small‐molecule mimics of ClpX that bind into hydrophobic pockets on the apical site of the complex, thereby activating ClpP. Detection of ClpP has so far been facilitated with active‐site‐directed probes which depend on the activity and oligomeric state of the complex. To expand the scope of ClpP labeling, we took a stepwise synthetic approach toward customized ADEP photoprobes. Structure–activity relationship studies with small fragments and ADEP derivatives paired with modeling studies revealed the design principles for suitable probe molecules. The derivatives were tested for activation of ClpP and subsequently applied in labeling studies of the wild‐type peptidase as well as enzymes bearing mutations at the active site and an oligomerization sensor. Satisfyingly, the ADEP photoprobes provided a labeling readout of ClpP independent of its activity and oligomeric state. Abstract : Antibiotic potential : Caseinolytic protease P (ClpP) is a peptidase that can gain proteolytic activity together with an ATPase. Acyldepsipeptides (ADEPs) mimic those, and thereby induce the activation of ClpP. The detection of ClpP has been realized with active‐site‐directed probes such as D3. Following SAR studies, we developed an ADEP photoprobe that is able to detect ClpP in its inactive form as well.